The Impact of Organizational Culture and Organizational Commitment on Employee Performance: A Mediation Study of Pt Abc's Job Satisfaction - Anggriyani, Yuli; Iskandarini, Iskandarini; Pohan, Vivi Gusrini R (Universitas Syiah Kuala, 2025)
This study aims to analyze the impact of organizational culture and organizational commitment on employee performance with job satisfaction as a mediating variable at PT ABC. The research approach uses a qualitative method by involving 20 employee resource persons selected through purposive sampling. Data were collected through in-depth interviews, participatory observations, and documentation, then analyzed using Miles and Huberman's interactive model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that a collaborative and open organizational culture and high affective commitment encourage the emergence of employee job satisfaction. Job satisfaction was found to be a significant mediating factor, where satisfied employees tended to demonstrate proactive performance, discipline, and high loyalty. In contrast, dissatisfied employees tend to work to minimum standards. Financial aspects and promotional opportunities emerged as factors that needed to be improved to strengthen overall job satisfaction. In conclusion, organizational culture and organizational commitment have a positive effect on employee performance through job satisfaction as a mediator. The practical implications of this research encourage PT ABC's management to strengthen a culture of innovation, provide recognition, and optimize the compensation system to support sustainable performance.